The effect of 4-week stroboscopic training on visual function and sport-specific visuomotor performance in top-level badminton players - Hülsdünker, T.; Rentz, C.; Ruhnow, D.; Käsbauer, H.; Strüder, H. K.; Mierau, A. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Stroboscopic training is suggested to improve visuomotor abilities in sports. However, previous research has primarily focused on untrained participants and only considered behavioral data. Because visuomotor performance is substantially determined by neural visual processes, this study aimed to examine the effects of stroboscopic training on visuomotor performance and neural visual function of athletes. Methods: A total of 10 German top-level badminton players (intervention: n = 5 and control: n = 5) participated in this study. Over a 4-week training period, athletes performed badminton-specific visuomotor tasks either wearing shutter glasses (intervention) or under normal visual conditions (control). Prior to and after the training period, behavioral smash-defense tests and neurophysiologic investigations of the N2 motion onset visual evoked potential were used to identify modulations in the athletes' visuomotor performance and visual perception speed, respectively. Results: Badminton training improved visuomotor performance in both groups; however, stroboscopic training resulted in superior posttraining performance compared with normal visual conditions (P = .007). Training-induced modulations in N2 latency did not reach significance, although a strong relationship was observed between changes in N2 latency and changes in visuomotor performance (r = -.55), indicating that higher performance gains following training were associated with a stronger reduction in N2 latency. Conclusions: The results indicate that stroboscopic training may be more effective than conventional visuomotor training for improving visuomotor abilities even in athletes performing at high skill levels. Furthermore, visuomotor performance gains could potentially be mediated by neural adaptations in the visual motion system. These findings should be confirmed for athletes from different disciplines.